Steady heat conduction of material with coated inclusion in the case of imperfect contact - Drygas, Paweł (Mathematical Modelling and Analysis, 2007)
We discuss a potential steady heat conduction for composites with the coated cylindrical inclusion under an imperfect contact condition. We rewrite equivalently the considered problem to a conjugation problem for analytic functions which is reduced then to functional‐differential equations. Solution of the obtained system of functional‐differential equations is given in the closed form.First Published Online: 14 Oct 2010